2012
DOI: 10.1002/jmor.20108
|View full text |Cite
|
Sign up to set email alerts
|

Description and scaling of pectoral muscles in ictalurid catfishes

Abstract: The pectoral spine of catfishes is an antipredator adaptation that can be bound, locked, and rubbed against the cleithrum to produce stridulation sounds. We describe muscle morphology of the pectoral spines and rays in six species in four genera of North American ictalurid catfishes. Since homologies of catfish pectoral muscles have not been universally accepted, we designate them functionally as the spine abductor and adductor and the arrector dorsalis and ventralis. The four muscles of the remaining pectoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Many ostariophysine fishes have two or even three chambers, and we suggest that all chambers contribute to buoyancy but divisions likely indicate acoustic specializations. Note differences in the channel catfish Ictalurus punctatus and the blue catfish Ictalurus furcatus, which have, respectively, one and two chambers despite being in the same genus (Miano et al 2013). Piranhas and other characids (Ladich and Bass 2005) have a large anterior and a smaller posterior chamber.…”
Section: Amplitude Levels Offmentioning
confidence: 97%
“…Many ostariophysine fishes have two or even three chambers, and we suggest that all chambers contribute to buoyancy but divisions likely indicate acoustic specializations. Note differences in the channel catfish Ictalurus punctatus and the blue catfish Ictalurus furcatus, which have, respectively, one and two chambers despite being in the same genus (Miano et al 2013). Piranhas and other characids (Ladich and Bass 2005) have a large anterior and a smaller posterior chamber.…”
Section: Amplitude Levels Offmentioning
confidence: 97%
“…Larger fish produce louder calls at lower frequencies owing to a more massive pectoral girdle (Duvall, 2007) that would have a lower natural frequency. Both sweep duration and pulse duration increase with fish TL, and high-speed camera data indicate that time to abduct the spine increases in larger individuals, whose muscles are longer and should take longer to contract (Connaughton et al, 1997;Connaughton et al, 2000;Wainwright and Richard, 1995;Miano et al, 2013). The number of jerks and pulses per sweep as well as pulse rate decrease with fish size.…”
Section: Discussionmentioning
confidence: 99%
“…The swimbladder in the oyster toadfish has a thin septum containing a sphincter that separates anterior and posterior parts of the organ (Fänge and Wittenberg 1958), and Tracy indicated that this partitioning separated gas secreting and reabsorbing parts of the bladder (Tracy 1911). Note differences in the channel catfish Ictalurus punctatus and the blue catfish Ictalurus furcatus, which have, respectively, one and two chambers despite being in the same genus (Miano et al 2013). Many ostariophysine fishes have two or even three chambers, and we suggest that all chambers contribute to buoyancy but divisions likely indicate acoustic specializations.…”
Section: Amplitude Levels Offmentioning
confidence: 99%